2010
DOI: 10.1016/j.cell.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

NF1 Is a Tumor Suppressor in Neuroblastoma that Determines Retinoic Acid Response and Disease Outcome

Abstract: Summary Retinoic acid (RA) induces differentiation of neuroblastoma cells in vitro and is used with variable success to treat aggressive forms of this disease. This variability in clinical response to RA is enigmatic, as no mutations in components of the RA signaling cascade have been found. Using a large-scale RNAi genetic screen, we identify crosstalk between the tumor suppressor NF1 and retinoic acid induced differentiation in neuroblastoma. Loss of NF1 activates RAS-MEK signaling, which in turn represses Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
1
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(185 citation statements)
references
References 47 publications
(59 reference statements)
10
161
1
13
Order By: Relevance
“…3, A-C, the mRNA levels of RAR␤ were effectively suppressed by siRNA RAR␤#7, with the greatest knockdown efficiency being ϳ60%, and, to a lesser extent, by siRNA RAR␤#8. Consistent with early studies showing that RAR␤ is greatly inducible by RA in both HepG2 cells and human livers with no significant changes in RAR␣ and RAR␥ (39), RA treatment caused a ϳ3-fold increase in mRNA amounts of RAR␤, the bona fide target gene of RA (40). Knockdown of RAR␤ by siRNA resulted in a profound reduction in the basal and RAstimulated RAR␤ expression, suggesting that RA is a more efficacious RAR ligand in HepG2 cells.…”
Section: The Correlated Alterations Of Hepatic Rar and Fgf21 During Tsupporting
confidence: 70%
“…3, A-C, the mRNA levels of RAR␤ were effectively suppressed by siRNA RAR␤#7, with the greatest knockdown efficiency being ϳ60%, and, to a lesser extent, by siRNA RAR␤#8. Consistent with early studies showing that RAR␤ is greatly inducible by RA in both HepG2 cells and human livers with no significant changes in RAR␣ and RAR␥ (39), RA treatment caused a ϳ3-fold increase in mRNA amounts of RAR␤, the bona fide target gene of RA (40). Knockdown of RAR␤ by siRNA resulted in a profound reduction in the basal and RAstimulated RAR␤ expression, suggesting that RA is a more efficacious RAR ligand in HepG2 cells.…”
Section: The Correlated Alterations Of Hepatic Rar and Fgf21 During Tsupporting
confidence: 70%
“…Furthermore, expression of the gene for the Ras GTPase-activating protein (RasGAP) NF1 is also associated with neuroblastoma patient outcomes, and recent studies have identified a potential role for NF1 as a mediator of retinoid resistance in neuroblastoma cells [156]. Additional studies have demonstrated efficacy of the novel MEK inhibitor binimetinib in preclinical models of neuroblastoma [155,157], suggesting that RAS-MAPK pathway inhibitors may be effective in patients with relapsed neuroblastoma.…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 98%
“…One way cells can become resistant to RA-induced differentiation is by loss of RA target gene expression (20,21). To determine if ectopic MAML3 expression leads to the loss of RA-responsive gene expression, we integrated our ChIP-seq and transcriptome data.…”
Section: E Western Blot Analysis Of Maml3 Protein Levels In Gfp-infementioning
confidence: 99%
“…Loss of NF1 activates RAS signaling, which in turn represses ZNF423 expression, leading to RA resistance. Low expression levels of ZNF423 and/or NF1 in neuroblastoma patients predict poor outcome (21).…”
Section: Introductionmentioning
confidence: 99%